Intergenerational cycles of violence: Risk factors of child abuse victims who turned violent offenders growing up - Uktubara, Ade Lily Reakid Arin; Ichwan Hendariyanto, Vendy; Riskika, Haressa Lintang; Chusairi, Achmad (Polteknik Ilmu Pemasyarakatan, 2024)
Child abuse has profound consequences for survivors. It increases the the risk of brain disorder, emotional regulation, self-adjustment, learning, and memory disorders, and is correlated with anti-social interactions and violent behavior in adulthood. This research aims to understand how individuals who have experienced child maltreatment, committed a violent crime once they became an adult. A narrative method was used in this study. By illuminating how early-life victimization could shape the life of an individual, we hope to shed light and eventually prevent survivors of child maltreatment down a path of violence. Three violent offenders were the subjects of this study. Data collection methods in the form of semi-structured interviews and non-human sources of information were carried out on three perpetrators of criminal acts of murder and abuse which resulted in death. The results in this study were analyzed using thematic analysis in chronological order. It was revealed that there are several risk factors in the series of cases of criminal acts. Intergenerational transmission of multiple risk factors and the use of illegal drugs are the main causes of aggressive behavior and criminal acts.